Proses Pelaksanaan Jasa Keagenan Dalam Menunjang Pelaksanaan Kapal Pada Perusahaan PT. Snepac Agency Asia Surabaya - Reni Sriana Tumangger; Dirhamsyah Dirhamsyah; Yuna Sutria; Fadiyah Hani Sabila (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine how the process of implementing agency services in supporting ship services at the company PT. Snepac Agency Asia Surabaya in ship agency while docking at Tanjung Perak Port and also to find out what procedures are carried out by agents in serving ships that arrive or dock at the Port where there are many activities carried out by agents in handling a ship that arrives at the Port or leaves Tanjung Perak Port. The method used by the author for this paper is two methods, namely the field method (field research) where the author directly observes in the field for ship activities and ship docking procedures. Then the library method (library research) the author gets references from the campus library so that the writing is in accordance with the existing title. the process of implementing agency services in supporting ship services at the company PT. Snepac Agency Asia Surabaya has been efficient in serving incoming ships starting from the owner sending an email about the arrival of the ship to the agent so that PT. Snepac Agency Asia Surabaya prepares documents before the ship arrives, the relevant agencies for ship services arrive until the ship docking process until the ship leaves the Port where the agent and the ship have good communication so as to help and speed up the process of ship services needed.